A qualitative exploration of daily path and daily routine among people in Ukraine who inject drugs to understand associated harms - Jill Owczarzak; Jessie Chien; Karin Tobin; Alyona Mazhnaya; Olena Chernova; Tetiana Kiriazova (BMC, 2022)
Abstract Background Patterns of movement, heterogeneity of context, and individual space-time patterns affect health, and individuals' movement throughout the landscape is shaped by addiction, meeting basic needs, and maintaining relationships. Place and social context enable or constrain behavior and individuals use social networks and daily routines to accomplish individual goals and access resources. Methods This article explores drug use as part of daily routines and daily paths among people who inject drugs in Dnipro City, Ukraine. Between March and August 2018, we interviewed 30 people who inject drugs living in Dnipro City, Ukraine. Study participants completed a single interview that lasted between 1 and 2 hours. During the interview, participants described their daily routine and daily path using a printed map of Dnipro as a prompt. Participants were asked to draw important sites; give time estimates of arrival and departure; and annotate on the map the points, paths, and areas most prominent or important to them. Participants also described to what extent their daily routines were planned or spontaneous, how much their daily path varied over time, and how drug use shaped their daily routine. Results We identified 3 major types of daily routine: unpredictable, predictable, and somewhat predictable. Participants with unpredictable daily routines had unreliable sources of income, inconsistent drug suppliers and drug use site, and dynamic groups of people with whom they socialized and used drugs. Participants with predictable daily routines had reliable sources of income, a regular drug dealer or stash source, and a stable group of friends or acquaintances with whom they bought and/or used drugs. Participants with somewhat predictable daily routines had some stable aspects of their daily lives, such as a steady source of income or a small group of friends with whom they used drugs, but also experienced circumstances that undermined their ability to have a routinized daily life, such as changing drug use sites or inconsistent income sources. Conclusions Greater attention needs to be paid to the daily routines of people who use drugs to develop and tailor interventions that address the place-based and social contexts that contribute to drug-use related risks.